REPRESENTASI KEKUASAAN DALAM MEDIA MASSA ONLINE (STUDI MAJALAH DETIK.COM) - Auliya Arista (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
The study of the representation of power in mass media focused on the study of the online magazine detik.com. Based on the results of the analysis it can be concluded that the representation of language in the study of power magazine detik.com issue December and January there are four forms in the representation of power. These forms are (1) the representation of power through the elements of language, language diversity (2), (3) the style of the language, and (4) follow-up said. These forms of speech in the form of four very diverse depending on the content and the type of news. Representation of the dominant powers of the language used in the December issue of detik.com magazine and January is the representation of the languages of power through the language style. The style of language that is often used to represent or public authority that is the style of the language of the Hyperbola, eufeminis, and repressive. The language style of all three of the most dominating language style is hyperbole and repressive. Not only based on the contents of the text but discourse based on titles already reflected clear that detik.com magazine is a magazine that was fond of using the language style hyperbole. To facilitate understanding and a false assertion about hemp following analysis of the child depicted in the form of a chart.